Meningkatkan Hasil Belajar IPAS Menggunakan Model Pembelajaran Contektual Teaching Learning (CTL) pada Siswa Kelas IV MI MT Lengkok Tengak - Muhammad Hafizin; Nyoman Dantes; Desak Putu Parmiti (LPPM Institut Pendidikan Nusantara Global, 2026)
Low student learning outcomes at the elementary school level remain a persistent challenge, particularly in IPAS (Integrated Science and Social Studies) learning. This condition is influenced by both internal and external factors. Internal factors include students’ limited understanding of learning materials and their low level of active participation during the learning process. External factors are reflected in teacher-centered instructional practices and the lack of integration between learning content and students’ real-life contexts. These conditions result in low learning motivation and suboptimal learning outcomes. This study aimed to improve students’ learning outcomes through the implementation of the Contextual Teaching and Learning (CTL) model in Grade IV IPAS at MI MT Lengkok Tengak. The study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 25 students, comprising 16 male and 9 female students. The learning intervention was carried out by applying the CTL model, which emphasizes connecting learning materials with students’ real-life experiences and surrounding environment. Data were collected through classroom observations, learning outcome tests, and documentation. The collected data were analyzed using simple qualitative data analysis techniques. The findings showed a significant improvement in students’ learning outcomes, indicated by an increase in the percentage of learning mastery from 64% in Cycle I to 92% in Cycle II. Therefore, the application of the Contextual Teaching and Learning (CTL) model in Classroom Action Research was proven effective in improving IPAS learning outcomes of Grade IV elementary school students.